Differences Between Group and Individual Care Systems in Neurorehabilitation: Where Are We Headed? - Candoni, Gerardo (Revista del Hospital Italiano de Buenos Aires, 2024)
The demand for rehabilitation is growing; however, studies demonstrating the superiority of the group format do so through statistical significance, not clinical significance. Individual rehabilitation may provide better patient-therapist interaction and, therefore, may benefit some individuals.
Keywords: Individual Care Systems; Group Care Systems; editorial; Neurorehabilitation